Epilepsy and obstructive sleep apnea syndrome - Mohamad, Hazama (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2011)
frequently coexist. Epilepsy patients were found to be drowsier when compared with general population using the Epworth Sleepiness Scale. The aim is to study obstructive sleep apnea syndrome (OSAS) in epilepsy patients, as well as the prevalence of obstructive sleep apnea and the predictors of sleepiness among epileptics. This was a prospective cross sectional study in HUSM on patients already diagnosed and treated with epilepsy. The study was conducted from Nove1nber 2008 to April 20 I 0. The consented participants who fulfilled the criterias were interviewed using questionnaire regarding demographic data. symptoms of obstruct!ve sleep apnea and Epsworth Sleepiness Scale, followed by full ear, nose and throat examination and overnight polysomnography (PSG). Five of sixty participants (8.3o/o) were diagnosed with OSA and four of them were males. OSA was mild in one patient, moderate in two patients and severe in the other two. Age, neck circumference, ESS score and BMI were significantly associated with OSA (p value <0.05). Epilepsy-related risks (type of seizures, duration and type of AED) have no significant association with OSA. Forty- nine percent of the abnormal physical findings found in OSA group were related to deviated nasal septu1n and inferior turbinate hypertrophy. The prevalence of OSA among epilepsy patients is 8.3%. The use of Malay version of ESS scale is appropriate and effective in screening patients for OSAS. Future role of PSG as part of assessment in high risks epileptics is recommended. Trc~1tinent of OSAS improves the quality of life of epilepsy patients.